Isolated torsion of the fallopian tube in a 16-year-old girl: A case report and review of the literature - GeorgiosN. Kolovos; Emmy Meytap; Nicolas Samartzis; Dimitrios Rafail Kalaitzopoulos (Elsevier, 2019)
Torsion of the fallopian tube is when the tube twists on the axis created between the infundibulopelvic ligament and the utero-ovarian ligament. It most commonly presents with appendicitis-like symptoms, such as abdominal pain, nausea and vomiting. Because of its rarity and non-specific symptoms, it is usually misdiagnosed initially, which delays therapy, at the expense of the preservation of fertility. This case report of a 16-year-old girl who had never had sexual intercourse presents an example of the misdiagnosis of fallopian tube torsion. The definitive diagnosis was based on laparoscopy. We summarize our experience and provide our conclusions after reviewing the literature. Keywords: Tubal torsion, Adnexal torsion, Laparoscopic management